(untitled) (ENTHYMEMA, 2013)
By following the perspective whereby mythos and symbol offer the first linguistic medium for a confused and inarticulate experience, Ricœur steers clear not only from natural science, but also from human science and semiotics, to foster a humanist conception that relies on an hermeneutics of form and texts received from tradition.